2018
DOI: 10.1002/cnm.3160
|View full text |Cite
|
Sign up to set email alerts
|

Numerical evaluation of nonbonded piezo sensor for biomedical diagnostics using electromechanical impedance technique

Abstract: Directly bonded piezo sensor, conventionally employed in the electromechanical impedance (EMI) technique, although a proven candidate for structural health monitoring, is severely constrained in its application in the biomedical field due to its bonding requirement. In contrast, nonbonded piezo sensor (NBPS) provides a viable platform to assess the condition of human bones, tissues, and other biomedical subjects using the EMI technique without inflicting pain or irritation to the skin. The name NBPS was coined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…These studies showed that detect bio-structural variations such as; cracks, total fractures, a healing process, and osteoporosis, could be possible in the future. Srivastava et al [25] and Srivastava and Bhalla [26] proposed an experimental design for studying numerically the structural state of bones measuring in vitro bone specimens and an in vivo subject. The procedures were carried out using a piezo-patch coupled to an aluminum beam, which in turn is fixed to a removable assembly in the study specimens.…”
Section: Introductionmentioning
confidence: 99%
“…These studies showed that detect bio-structural variations such as; cracks, total fractures, a healing process, and osteoporosis, could be possible in the future. Srivastava et al [25] and Srivastava and Bhalla [26] proposed an experimental design for studying numerically the structural state of bones measuring in vitro bone specimens and an in vivo subject. The procedures were carried out using a piezo-patch coupled to an aluminum beam, which in turn is fixed to a removable assembly in the study specimens.…”
Section: Introductionmentioning
confidence: 99%
“…Experiments were performed on ex vivo healthy and osteoporotic femur bones with promising results. In [142], the authors assessed NBS and BS with finite element models of the radius and femur; they concluded that the simulations matched well the experimental results of their previous investigations [137,141,143].…”
Section: Current Stagementioning
confidence: 62%
“…It is important to note that the transducer sensitivity improvement from using the negative capacitance interface not only can be applied to detect structural damage in engineering structures but also can be extended to other fields of research that monitor variations in mechanical quantities by means of corresponding variations in the electrical impedance of transducers. Other fields of research that may employ the results presented here are biomedicine and dentistry with applications such as biomedical diagnostics [18], [19] and dental implant monitoring [20].…”
Section: B Damage Sensitivity Improvementmentioning
confidence: 97%